Differential effects of donor‐specific HLA antibodies in living versus deceased donor transplant. Issue 9 (16th April 2018) - Kamburova, E. G.; Wisse, B. W.; Joosten, I.; Allebes, W. A.; van der Meer, A.; Hilbrands, L. B.; Baas, M. C.; Spierings, E.; Hack, C. E.; van Reekum, F. E.; van Zuilen, A. D.; Verhaar, M. C.; et al.
Abstract : The presence of donor‐specific anti‐HLA antibodies (DSAs) is associated with increased risk of graft failure after kidney transplant. We hypothesized that DSAs against HLA class I, class II, or both classes indicate a different risk for graft loss between deceased and living donor transplant. In this study, we investigated the impact of pretransplant DSAs, by using single antigen bead assays, on long‐term graft survival in 3237 deceased and 1487 living donor kidney transplants with a negative complement‐dependent crossmatch. In living donor transplants, we found a limited effect on graft survival of DSAs against class I or II antigens after transplant. Class I and II DSAs combined resulted in decreased 10‐year graft survival (84% to 75%). In contrast, after deceased donor transplant, patients with class I or class II DSAs had a 10‐year graft survival of 59% and 60%, respectively, both significantly lower than the survival for patients without DSAs (76%). The combination of class I and II DSAs resulted in a 10‐year survival of 54% in deceased donor transplants. In conclusion, class I and II DSAs are a clear risk factor for graft loss in deceased donor transplants, while in living donor transplants, class I and II DSAs seem to be associated with an increased risk for graft failure, but this could not be assessed due to their low prevalence. Abstract : Via a retrospective multicenter study, the authors investigate the impact of pretransplant donor‐specific HLA antibodies on long‐term graft survival in deceased and living donor kidney transplantations.